SIMTOM DEPRESI PADA PASIEN PASCA STROKE DI RSUD DELI SERDANG - MUHAMMAD SHOLEHAN AKBAR; ANITA SURYA (LP2MTBM MAKARIOZ, 2021)
In ASEAN countries stroke is a major health problem that causes death. From the data from the South East Asian MedicalInformation Center (SEAMIC), it is known that the largest stroke mortality rate occurs in Indonesia, which is then followedsequentially by the Philippines, Singapore, Brunei, Malaysia and Thailand. Of all stroke patients in Indonesia, ischemicstroke is the most common type, which is 52.9%. The number of stroke patients in Indonesia is based on the 2010population and demographic census of 3,600,000 each year with a prevalence of 8.3 per 1,000 population. To determinewhether there are depression symptoms in post-stroke patients in Deli Serdang Hospital. Descriptive study using aquestionnaire. The prevalence of depression symptoms in post-stroke patients was found mostly in mild depressivesymptoms of 28 people (56%). Based on the demographic characteristics of the most genders, there were 27 women (54%),for the highest age> 60 years as many as 23 people (46%), and the most common education in high school education was26 people (52% ) While the types of strokes that were most commonly found in depressive symptoms in post-stroke patientswere ischemic stroke as many as 42 people (84%). Depressed symptoms were found in post-stroke patients at Deli SerdangHospital.